Effect of Some Thioureas on the Corrosion of 1100 Aluminium in Acidic Chloride Solution. - YADAV, P.N.S.; WADHAWANI, R. (Asian Journal of Chemistry, 2010)
The effect of urea, thiourea and some of its derivatives namely phenyl thiourea, o-tolyl thiourea, m-tolyl thiourea, p-tolyl thiourea, 1:3-di-o-tolyl thiourea, 1 :3-di-m-tolyl thiourea and 1:3-di-p-tolyl thiourea on the corrosion of 1100 aluminium has been studied in 1% hydrochloric acid using different concentrations of the compounds at 25º,35º and 45ºC. The inhibition efficiencies of the inhibitors were found to increase with increase in temperature from 25º to 45ºC. Better inhibition was given by all compounds for 48 h exposure period.